Field host range of Apanteles opuntiarum (Hymenoptera: Braconidae) in Argentina, a potential biocontrol agent of Cactoblastis cactorum (Lepidoptera: Pyralidae) in North America - Varone, Laura (2015)
Field exploration in Argentina for cactophagous lepidopteran hosts parasitized by the recently described braconid parasitoid Apanteles opuntiarum Martínez & Berta (Hymenoptera: Braconidae) revealed a host range restricted to Cactoblastis cactorum (Berg) (Lepidoptera: Pyralidae) and C. doddi. Field collections of cactophagous larvae parasitized by the congeneric and sympatric parasitoid A. alexanderi included the host species C. bucyrus, Sigelgaita nr. chilensis, Tucumania sp., Tucumania tapiacola and Salambona sp. If a narrow host range for A.opuntiarum is confirmed in quarantine with North American cactus-feeding species, then this parasitoid could be released as a biological control agent for C. cactorum with little or no risk to non-target species.